Pharmaceutical properties of novel 3-((diisopropylamino)methyl)-5-(4-((4-(dimethylamino) benzylidene) imino) phenyl)-1,3,4-oxadiazole-2(3 H)-thione - Khalida F. Al-azawi; Butheina A. Hasoon; Raid A. Ismail; Khetam H. Rasool; Majid S. Jabir; Suaad S. Shaker; Kareem H. Jawad; Ahmed Mutanabbi Abdula; Suresh Ghotekar; Ayman A. Swelum (Scientific Reports)
Abstract The synthesis of novel chemical compounds is crucial for developing new pharmaceuticals and antimicrobial agents. The Mannich reaction, involving Maunch bases known as carrier beta-amino-ketone molecules, is significant for producing nitrogen-containing compounds. This study investigates a new compound for its potential biological activities, particularly its antibacterial and anticancer properties. A new chemical compound, (3-((diisopropylamino)methyl)-5-(4-((4-(dimethylamino)benzylidene)imino)phenyl)-1,3,4-oxadiazole-2(3 H)-thione) (DMDBIPOT), was synthesized through the Mannich reaction, where 1,3,4-oxadiazole-2-thiol derivatives reacted with various secondary amines and formaldehyde. The compound was characterized using FTIR, 1 H NMR, and 13C NMR spectroscopy. Its antibacterial activity was tested against Klebsiella pneumoniae isolates, and its antioxidant properties were evaluated using the DPPH assay. Additionally, the anticancer activity was assessed using the MTT assay on the PC-3 prostate cancer cell line and in silico study. The synthesized compound exhibited strong antibacterial activity against K. pneumoniae, significantly outperforming Amikacin (P ≤ 0.05). It effectively prevented biofilm formation on urinary catheters, confirmed by atomic force microscopy (AFM). The findings indicate that DMDBIPOT effectively inhibits microbial biofilm growth, suggesting its potential as a preservative for Foley catheters. The DPPH assay demonstrated that higher concentrations of the compound resulted in greater free radical scavenging activity. Furthermore, the MTT assay showed significant cytotoxic effects against PC-3 cells, indicating that the compound stimulates programmed cell death. The docking study confirmed the interaction of DMDBIPOT with the target binding pocket, validating its efficacy as a therapeutic agent. The findings suggest that the novel chemical compound possesses potent antibacterial properties and exhibits significant anticancer activity by interacting with DNA and inducing apoptosis in cancer cells. These results highlight the potential clinical applications of the compound in treating infections and cancer. This study presents a novel chemical compound synthesized through the Mannich reaction, demonstrating promising antibacterial and anticancer activities. The compound’s ability to inhibit biofilm formation and induce cytotoxic effects suggest that it as a candidate for future therapeutic development.